Justiça Sanitária: cidadãos e judiciário nas reformas urbana e sanitária - Rio de Janeiro (1904 1914) - Queiroz, Eneida Quadros (2008)
This Project deals with the urbane reforms and sanitary dispositions in Rio de Janeiro, between 1904 - 1914. It focus on the fight for rights and Justice among the city s changes. It analyzes how people used to fight for their rights in Justice when they were hit by the sanitary dispositions. Analyzing criminal lawsuits and civil lawsuits from Sanitary Justice it shows what were the meanings of Justice for people at that time, who were using Justice as a open field to fight for their rights. It analyses for what reasons people looked for Justice and what where their expectative. At the end, it analyzes what were the kind of gains or loss for those people who looked for Justice. There were been analyzed unpublished primary sources, Federal Justice s lawsuits and Sanitary Justice s lawsuits between the years of 1904 1914.